Maksimalisasi Kinerja Pengolahan Sampah Domestik dengan Penguatan Kapasitas Organisasi TPS3R di Kelurahan Blimbing Lamongan - Majid, Abdul; Lailiyah, Elliv Hidayatul; Ramadani, Aisyah Hadi; Solekha, Rofiatun; Yaumi, Sri (ABDI DAYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Blimbing sub-district is projected in the regional development plan as the center of the Minapolitan economy in the northern region of Lamongan, however this area has problems with waste management conditions so that it is included in an urban slum area. The effort that has been made is the construction of a communal waste collection site in the form of TPS 3R. However, the utilization of TPS 3R is not optimal, the waste input is only 8%, but the TPS capacity is full. This condition indicates the need to manage organic and inorganic waste quickly and efficiently. The lack of understanding of the group responsible for the TPS has resulted in ineffective waste management performance in Blimbing Village. This community service activity aims to provide assistance in strengthening the management of the TPS3R organization so that waste management performance in Blimbing Village can be active again. The method used uses the PAR (participation action research) approach. The activity stages include Socialization, Focus Group Discussion, Mediation, and Training. Training in this service takes the form of organizational management, orderly financial administration, magot cultivation and diaper waste processing. The result of this community service is an increase in understanding of waste management by 45 to 60 percent.